1991
DOI: 10.1007/bf01945426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of phenolic compounds on CCl4-induced microsomal lipid peroxidation

Abstract: The antiperoxidative effects of 35 phenolic compounds, most of them belonging to the flavonoid class, were investigated using CCl4-induced peroxidation of rat liver microsomes. This system was rather insensitive to gallic acid, methyl gallate and ellagic acid. Nevertheless it was inhibited by flavonoids and structure/activity relationships were established. The most potent compounds were gardenin D, luteolin, apigenin (flavones), datiscetin, morin, galangin (flavonols), eriodictyol (flavanone), amentoflavone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
5

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(137 citation statements)
references
References 14 publications
6
125
0
5
Order By: Relevance
“…They are strong antioxidants that occur naturally in foods and can inhibit carcinogenesis in rodents [5,6]. Acacetin (5,7-dihydroxy-4 0 -methoxyflavone), a flavonoid compound, has been reported to possess antiperoxidative, anti-inflammatory, and antiplasmodial effects [7][8][9], and to enhance differentiation-inducing activity in HL-60 cells [10]. In addition, acacetin can also inhibit glutathione reductase, cytochrome P450, and topoisomerase I-catalyzed DNA religation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They are strong antioxidants that occur naturally in foods and can inhibit carcinogenesis in rodents [5,6]. Acacetin (5,7-dihydroxy-4 0 -methoxyflavone), a flavonoid compound, has been reported to possess antiperoxidative, anti-inflammatory, and antiplasmodial effects [7][8][9], and to enhance differentiation-inducing activity in HL-60 cells [10]. In addition, acacetin can also inhibit glutathione reductase, cytochrome P450, and topoisomerase I-catalyzed DNA religation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although no 3 0 -hydroxyl group, there is a 3 0 -methoxyl group contained in typhaneoside and I3ON, which also forms the hydrogen bonds. Additionally, a previous study has demonstrated that glycosylation at position 7-OH or 8-OH, but not 3-OH, could impair the antioxidant effect of flavonoids (Cholbi et al 1991). Thus, the significant antioxidant effect of the pollen should be owing to the structure characteristics of these compounds in the aquatic plant pollen.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, VCO possessed this activity hence may be one of the potential candidate for gastroprotection. Moreover, those oils might also work via several other mechanisms of gastroprotection such as by increasing gastric hexosamine level and enhancing the strength of the gastric barrier either physically or by blocking the H + ,K + -ATPase pump, stimulation of membrane stabilization by interference with Ca + influx and inhibition of biological membranes (Akhtar et al, 1992;Akhtar and Ahmed, 1995;Cholbi et al, 1991;Koch and Loffler, 1985). Further study is, therefore, required to confirm on the possible mechanisms of gastroprotection used by the VCOs to demonstrate the antiulcer activity.…”
Section: Discussionmentioning
confidence: 99%